Hemodynamic effects of zinc sulfate on anesthetized open-chest dogs - Ma Feng-jun; Zhao Geng-sheng; Li Xiao-guang (Acta Pharmacologica Sinica; Vol 10, No 3 (May 1989): Acta Pharmacologica Sinica, 2016)
ZnSO4 3-5 mg/kg iv decreased systolic blood pressure, diastolic blood pressure and mean arterial blood pressure, +dP/dtmax, -dP/dtmax, VCE- +dP/dtmax, and left ventricular systolic pressure. However, ZnSO4 had no significant effects on T values and total peripheral resistance. In addition, ZnSO4 obviously decreased heart rate and cardiac index. These results suggest that iv ZnSO4 may cause hypotension via cardiac inhibition.